G37(P) Laboratory correlates of severity in acute bronchiolitis of infancy. (12th March 2018) - Ghazaly, M; Thwaites, R; Feather, K; Ito, K; RapePort, G; Openshaw, P; Hansel, T; Nadel, S
Abstract : Introduction: Respiratory viral infections cause significant morbidity and mortality in infants; approximately half of which are associated with respiratory syncytial virus (RSV) infection. Severe bronchiolitis has been associated with an aberrant host response to viral replication. We investigated the patient characteristics, immune response and viral load in bronchiolitis. Methods: We recruited patients<2 years of age presenting to St Mary's Hospital between October 2016–March 2017 with a clinical diagnosis of bronchiolitis. We recruited 55 hospitalised babies; grouped into moderate (n=34) and severe (n=21) based on their need for invasive respiratory support. Respiratory samples were collected up to twice daily using nasosorption and nasopharyngeal aspiration (NPA) along with severity scores (PEWs, M-WCAS, and RESVINET). Viral load was determined by qPCR (Primer Design, UK), immune mediators were quantified by MSD (MSD, Rockville, USA). Results: Younger age, lower weight and more co-morbidities were observed among severe cases; 50% had apnoea on presentation. Taking disease duration into account, viral load was observed to be significantly lower in severe RSV cases, compared to moderate cases, although decline in viral load was quicker (table 1). Levels of IFN-γ and CXCL10/IP-10 were significantly higher in moderate versus severe cases. Levels of many inflammatory mediators (including type-II cytokines) were not significantly different between groups whilst mucin levels were elevated in severe cases. Conclusion: A strong innate anti-viral immune response early in disease may protect against severe RSV disease, despite higher viral load. Detailed study of airway mucosal responses to infection may clarify determinants of severity in bronchiolitis.